Optimalisasi Modal Psikologis dalam Pemberdayaan Sumber Daya Manusia untuk Meningkatkan Kinerja berkelanjutan UMKM - Frederick Rudy Sentosa Rajagukguk; Hastuti Handayani Harahap; Indra Welly Arifin (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2026)
This study aims to analyze the effect of Psychological Capital on Sustainable Performance of MSMEs through Human Resource Empowerment as an intervening variable. This research uses a quantitative approach with a survey method. The sample consisted of 120 MSME respondents selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (SmartPLS). The results show that Psychological Capital has a positive and significant effect on Sustainable Performance of MSMEs, Psychological Capital has a positive and significant effect on Human Resource Empowerment, and Human Resource Empowerment has a positive and significant effect on Sustainable Performance of MSMEs. In addition, Human Resource Empowerment is proven to mediate the relationship between Psychological Capital and Sustainable Performance of MSMEs. The Goodness of Fit value indicates a good model fit. In conclusion, enhancing psychological capital and optimizing human resource empowerment are important factors in improving the sustainable performance of MSMEs.